Enhancing Psychological Recovery of Natural Disaster Victims: Tuan Guru's Contribution in Aek Natas, North Sumatra - Ramadhan, Wirawan; Syawaluddin, Syawaluddin (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2024)
Natural disasters not only cause physical damage but also significantly impact the psychological well-being of victims. This is evident in Aek Natas District, Labuhanbatu Utara Regency, North Sumatra Province, where flash floods have resulted in both material and psychological losses. Unlike material losses, which people can recover through various efforts, psychological trauma is more challenging to address. A key figure in this context is the kiai or Tuan Guru. This study aims to examine the role of the kiai or Tuan Guru in restoring the psychological well-being of disaster victims in Aek Natas District, Labuhanbatu Utara Regency, North Sumatra Province. The research uses a qualitative approach. Data collection techniques include observing Tuan Guru's activities, conducting direct interviews with Tuan Guru Syeikh H. Syamsuddin Hasibuan, a local spiritual leader, and interviewing community members affected by the disaster. Additional data come from documents and records related to the disaster, which provide further context to the interview and observation results. The study finds that natural disasters cause psychological damage, such as trauma. Addressing the psychological needs of disaster victims, the role of Tuan Guru proves crucial. Tuan Guru H. Syamsuddin Hasibuan contributes to the psychological recovery of disaster victims in Aek Natas by offering spiritual guidance, providing emotional support through counseling, building community, and delivering training and education. The main contribution of this research is developing and implementing a community-based approach that integrates social support, education, and practical training as a holistic and adaptive strategy for psychological recovery.